Friction aided deep drawing of sheet metals using polyurethane ring and auxiliary metal punch. Part 2: analysis of the drawing mechanism and process parameters - Hassan, M.A.; Hino, K.; Takakura, N.; Yamaguchi, K. (2002)
Friction aided deep drawing using a polyurethane ring as a pressure medium has been analyzed by the slab and the energy methods to understand the main features of the process and to find the optimum conditions to achieve successful drawing. The effect of an auxiliary metal punch on the stress distribution of the deformed blank and the increase in height of the drawn cup is also discussed. From these studies, the reason why the unusual circumferential crack occurs at the flange of the deformed blank has been clarified, based on the radial stress distribution of the deformed blank. A process parameter, which denotes the drawing characteristics of the friction aided deep drawing, has been proposed. In addition, the drawing region diagram has been presented to facilitate the drawing pressure control with the progress of the drawing process. It is shown that the successful drawing region is narrow at the early stage of drawing, although it becomes wide as the drawing proceeds. Therefore, in the early stage of drawing, special care should be paid to the drawing pressure control to avoid the flange crack. (C) 2002 Elsevier Science Ltd. All rights reserved.